Penguatan Model Bisnis PT. Parlevliet Paraba Seafood Menggunakan Triple Layered Business Model Canvas - Rosadila Ainul Qodri; Otto Randa Payangan; Andi Nur Baumassepe (Magister Management, Hasanuddin University, 2019)
This research aims to (1) know the description of PT. Parlevliet Paraba Seafood in creating, sending, and capturing values ​​on economic, environmental, and society using Triple Layered Business Model Canvas. (2) Formulate a strategy using SWOT Analysis that can be applied based on the description of Triple Layered Business Model Canvas PT. Parlevliet Paraba Seafood. (3) Knowing the results of alternative strategy recommendations using SWOT Analysis in the Triple Layered Business Model Canvas that can be implemented by PT. Parlevliet Paraba Seafood. This type of research is qualitative research. In this study, primary data sources came from observations and informants related to PT. Parlevliet Paraba Seafood (stakeholders). Secondary data obtained from various literature and related research results. Data collection techniques are carried out by observation, interview, documentation and triangulation. The results of the study show that the business of creating, capturing, and sending values ​​to the three layers of sustainable concepts is the Economic Layer: (1) Partner, the company does not have a cooperative relationship with suppliers. (2) Activities, key activities are on purchases. (3) Resources, key resources are in raw materials. Environment Layer: (1) Supplies and Out-Sourcing, namely water, ice, electricity and soap. (2) Production, there are no production activities that affect the environment. (3) Materials, there are no raw materials that affect the environment. Layer Society; (1) Local communities, which carry out the development of fishermen. (2) Governance, which is a centralized decision and lacks transparency in decision making. (3) Employees, which are positive workplaces. (4) Social value, namely service to suppliers and economic activities around the company.